A Systematic Literature Review on Character Education Strategies in Primary and Secondary Schools - Hadi, Yulianto; Kholis, Nur; Remanita, Yuan; Harta, Lilik Indri (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Character education is important in developing 21st-century education, especially at the elementary and secondary school levels. However, its implementation still faces conceptual and operational challenges in various countries. This study conducted a systematic literature review (SLR) of 35 articles published between 2019 and 2024 from the Scopus, DOAJ, and Google Scholar databases. Article selection followed the PRISMA guidelines with specific inclusion criteria. The analysis revealed four main themes: value-based learning approaches, teacher involvement, the role of the school environment, curriculum integration, and implementation barriers. A trend toward increased collaborative approaches was identified, but teacher training and character evaluation systems remain challenges. This study recommends strengthening the character education ecosystem by involving schools, teachers, and communities holistically and contextually.